Representasi Nilai Pendidikan Akhlak Tasawuf Dalam Novel Kembara Rindu Karya Habiburrahman El Shirazy - Fatmawati Fatmawati (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2022)
Moral decadence is caused by alienation as a result of modernization. The solution to this problem is the need for Sufism moral education. The values of Sufism moral education contained in a literary work can provide enlightenment for humans because literature has a more sensitive feeling. This study aims to describe the representation of the value of Sufism moral education in the novel Kembara Rindu by Habiburrahman El Shirazy. This research is in the form of descriptive qualitative using the content analysis technique as an assessment strategy. The data analysis method used is Miles and Huberman's interactive data analysis. The results of this study are: (1) the representation ofÂ  the value of Sufism moral education in the novel Kembara Rindu by Habiburrahman El Shirazy is described through the behavior of the characters contained in the novel. The representation of the value of Sufism moral education in the form of the value of wisdom (al-hikmah) includes the behavior of intelligence sharpness and clarity of thought, the value of maintaining chastity (al-iffah) includes the behavior of generosity, determination, and virtuousness, the value of courage (al-syaja'ah) includes calm and patient, the value of justice (al-adl') includes the behavior of love, friendship, and tawadhu; (2) this research has implications for other relevant aspects in the form of: theoretical implications, namely opening up insight into the variety of novels that can be used as learning media; the pedagogical implication is that the novel Kembara Rindu can be used as a learning medium; and the practical implication is that this research can enrich the treasures of science.